156 Long-term effects of perampanel on cognition, growth/development in paediatric patients with epilepsy study 311. Issue 6 (27th May 2022) - Ben Renfroe, J; Patten, Anna; Malhotra, Manoj; Ngo, Leock Y
Abstract : Background: The long-term (≤1-year) effects of adjunctive perampanel on cognition, behaviour and growth/development were assessed in paediatric patients aged 4–<12 years with partial-onset seizures (POS) (with/without secondarily generalised seizures [SGS]) or primary generalised tonic-clonic seizures (PGTCS) during Study 311 (NCT02849626 ). Methods: Core Study (4-week pretreatment/23-week treatment) completers could enter the Extension (29-week maintenance/4-week follow-up). Assessments included: change from baseline at Week 52 for cognition (Aldenkamp-Baker Neuropsychological Assessment Schedule [ABNAS]), behavioural/emotional problems (Child Behaviour Checklist [CBCL]), visuomotor skills (Lafayette Grooved Pegboard Test [LGPT]) and growth/development. Results: Mean standard deviation (SD) change from baseline to Week 52 in total ABNAS score was -3.3 (16.6) (n=112). Mean (SD) change from baseline at Week 52 in CBCL total problems was -6.0 (14.0) and -1.6 (14.7) for patients aged 1.5–5 (n=17) and 6–18 years (n=102), respectively; for time to complete the LGPT, this was 5.3 (48.0) seconds for patients aged ≤8 years (n=33) and 0.4 (23.2) for patients aged >8 years (n=51). No significant impact on growth/development observed. Conclusion: No clinically significant changes were observed in cognition, behaviour or growth/devel- opment parameters following long-term (≤1 year) adjunctive perampanel in paediatric patients (aged 4–<12 years) with POS, SGS or PGTCS. Funding: Eisai Inc. manoj_malhotra@eisai.com